Employer's expectation to QS graduates in facing Industrial Revolution 4.0 / Mohamad Zaifulzaki Kamde ... [et al.] - Kamde, Mohamad Zaifulzaki; Mamter, Shahela; Mamat, Mohd Esham; Abdullah@Dolah, Noor Anisah (2022)
Currently, the construction industry is facing a new phase of the industrial revolution where computers and robotics are implemented around the midst of the revolution thus bringing new technology that can give many benefits to the construction industry. Along with the transition to the new revolution, customer needs and demand in the construction industry have been more diverse and more complicated. Thus, professional personnel in the construction industry which also included quantity surveyors (QS) must be trained with relevant expertise and competencies while being committed to the ongoing growth and application of new skills. Past studies that have examined the lack of benchmarking of the competencies required have left many parties in the industry unsettled. These issues are the focal point of this study. Therefore, the study objectives are to identify employer's expectation on the effect of lacking quantity surveying graduates' competencies in facing IR 4.0 and to recommend the employer's initiatives to improve quantity surveyor competencies in facing IR 4.0. The distribution of the 250 sets of questionnaires took place randomly to construction organisations registered with CIDB in Johor. This study reveals that employers expect that a stagnant increase in QS salary and underpaid among QS was the most significant effect of lacking quantity surveying graduates' competencies in facing IR 4.0 and employers agreed to send their staff to a training program are the best initiatives to develop their competencies to match with the competency required to face IR 4.0. From this study, it can be concluded that many effects can influence the QS profession due to a lack of competencies.